URGENT AND LAG PSYCHOPHYSIOLOGICAL EFFECTS NEUROFEEDBACK IN SPORTSMEN OF HIGH QUALIFICATION - O. V. Kaigorodtseva (Bûlleten' Sibirskoj Mediciny, 2013)
The article provides a comparative analysis of the psychophysiological state of sportsmen of high qualification within one year after the course neurofeedback. These data demonstrated that high qualification sportsmen physiological effects of training persist throughout the year and depend on the ability to arbitrarily increase the power of the alpha rhythm of the brain.